2015
DOI: 10.1159/000381754
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial Comparing the Effects of Vessel Sealing Device and Milligan Morgan Technique on Postoperative Pain Perception after Hemorrhoidectomy

Abstract: Background: The aim of this study was to compare postoperative pain perception after Milligan Morgan and Ligasure™ techniques in hemorrhoidectomy. Methods: Fifty-four patients diagnosed with Grade 3-4 hemorrhoids requiring surgery between May 2013 and September 2013 were enrolled in the study. Patients were randomized into either the Ligasure™ hemorrhoidectomy group (Group 1, n = 26) or the Milligan Morgan hemorrhoidectomy group (Group 2, n = 28). Results: The difference between visual analogue scale scores on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Dietary modification, counseling regarding defecation habits and office-based procedures (banding, sclerotherapy and infrared coagulation) could help most patients relieve hemorrhoid symptoms [ 3 , 4 ]. However, for grade 3–4 hemorrhoid patients, surgical treatments are often unavoidable [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary modification, counseling regarding defecation habits and office-based procedures (banding, sclerotherapy and infrared coagulation) could help most patients relieve hemorrhoid symptoms [ 3 , 4 ]. However, for grade 3–4 hemorrhoid patients, surgical treatments are often unavoidable [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the guideline statements from different countries such as Italy (3), Japan (4), and many other countries (5)(6)(7), for patients with grade IV hemorrhoids, Milligan-Morgan open hemorrhoidectomy is still one of the standard procedures (8). The frequently encountered one after open hemorrhoidectomy is postsurgical pain (9,10). In clinical practice, the size of the surgery area and the psychological states may all affect the degree of postsurgical pain (11).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional hemorrhoidectomy involving both closed and open techniques is considered the gold standard for prolapse piles globally. Recent studies showed the superiority of other techniques like HS and BD over traditional surgery [ 4 , 5 ]. A bipolar diathermy device is an anti-hemorrhagic tool and can deliver a precise amount of electrocautery energy across vascular structures with minimal surrounding thermal spread [ 3 ].…”
Section: Introductionmentioning
confidence: 99%